2022
DOI: 10.3389/fcvm.2022.901225
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Aortic Aneurysm and Its Attributable Risk Factors from 1990 to 2019: An Analysis of the Global Burden of Disease Study 2019

Abstract: BackgroundGlobal and national estimates on the epidemiology of aortic aneurysms are prerequisites for disease management and policymaking. Based on the Global Burden of Disease (GBD) 2019, this study aimed to discern the global aortic aneurysm burden by systematically analyzing demographic data on mortality and exploring the attributable risks and relevant factors.MethodsThe data analyzed in this study were available in the Global Health Data Exchange (GHDx) online query tool. The population in our study compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Definitive proof for the contributions of such skewed X-inactivation to AS phenotype in females has not yet been achieved and is an active area of study [ 20 ]. Aortic aneurysm in the absence of AS or other underlying genetic risk factor is much more prevalent in elderly subjects reflecting the progressive and accumulative influence of other known risk factors (hypertension, atherosclerosis, inflammation) on aortic wall function [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive proof for the contributions of such skewed X-inactivation to AS phenotype in females has not yet been achieved and is an active area of study [ 20 ]. Aortic aneurysm in the absence of AS or other underlying genetic risk factor is much more prevalent in elderly subjects reflecting the progressive and accumulative influence of other known risk factors (hypertension, atherosclerosis, inflammation) on aortic wall function [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Nutritionist-Dietitian in the Abdominal Aortic Aneurysm O dietista-nutricionista face ao aneurisma da aorta abdominal Rafael Almendra-Pegueros 1,2* , José Martínez-González [2][3][4] , Cristina Rodríguez [1][2][3] , María Galán [1][2][3]5 https://doi.org/10.35454/rncm.v5n3.435…”
Section: El Nutricionista-dietista Ante El Aneurisma De Aorta Abdominalmentioning
confidence: 99%
“…De acuerdo con el informe Global Burden of Disease Study 2019, el aneurisma aórtico (AA) provocó 172 427 muertes durante 2019, observándose un incremento del 82,1 % desde 1990. Este incremento fue inferior en países con mayor índice sociodemográfico (33,47 %), mientras que, en las regiones de menores ingresos y mayores desigualdades sociales, el problema persiste (1,2) . Los AA son dilataciones focalizadas de la aorta que se pueden localizar a nivel del tórax (AA torácico) y a nivel abdominal (AAA), siendo este último el más común (3) .…”
Section: El Nutricionista-dietista Ante El Aneurisma De Aorta Abdominalunclassified
“…We hypothesise that meaningful cardiovascular measurements can be extracted from UKBB abdominal MRI, and that these measurements may provide new insights into the etiology of a range of cardiovascular disease outcomes including the detection of abdominal aortic aneurysm (AAA) during routine clinical investigations, a condition that continues to be a significant cause of clinical complications and death. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesise that meaningful cardiovascular measurements can be extracted from UKBB abdominal MRI, and that these measurements may provide new insights into the etiology of a range of cardiovascular disease outcomes including the detection of abdominal aortic aneurysm (AAA) during routine clinical investigations, a condition that continues to be a significant cause of clinical complications and death. 5,6 Previous studies have demonstrated that CMR IDPs in the UKBB, including diameter of the ascending and descending aorta 7 and ventricular volumes, 8 have a substantial heritable component. The cross-sectional areas (CSAs) of vessels represent different partitions in the body receiving blood supply and their sizes are associated with variation in blood supply, blood pressure, age and body size.…”
Section: Introductionmentioning
confidence: 99%